Revelation - Garrow, A. J. P. (Alan John Philip), 1967- (New Testament readings., 1997)
This study seeks a way of understanding Revelation by analysing the structure of the book. Emphasising the context of 'reading aloud' - in installments - Alan Garrow uses the historical circumstances to elucidate the genre of the book.